OPTIMALISASI PELAYANAN BERBASIS DIGITAL QRIS UNTUK MENINGKATKAN PEROLEHAN DANA ZAKAT, INFAK DAN SEDEKAH DI LAZ SIDOGIRI - Abdillah Mundir; Uyun Nabila (Jurnal Ekonomi Syariah Darussalam, 2023)
The purpose of this study is to determine the optimization of QRIS-based digital services implemented by the Amil Zakat Sidogiri Institute to increase the acquisition of zakat, infak and alms funds. The research methodology used is descriptive qualitative research. From the results of the study, it can be concluded that the optimization of QRIS-based digital-based services implemented by the Amil Zakat Sidogiri Institute in an effort to increase the acquisition of zakat, infak and alms funds has increased significantly, as in interview statements and the results of the calculation of the increase curve which illustrates an increase of more than 3 billion each year, although there are still some obstacles experienced by the Sidogiri Amil Zakat Institute in an effort to raise zakat funds infak and alms that make ZIS funds are still far from the projections set, Therefore, several efforts are needed in promoting QRIS-based digital services implemented by the Amil Zakat Sidogiri Institute through several media such as social media, so that the public is more familiar with the Amil Zakat Sidogiri Institute and is moved to pay their ZIS funds through the QRIS service implemented by the Amil Zakat Sidogiri Institute.